Characterization of the effect of CFRP reinforcement on the fatigue strength of aluminium alloy plates with fastener holes. (15th December 2018) - Wang, Zhi-Yu; Zhang, Tao; Li, Xiaolei; Wang, Qing-Yuan; Huang, Wanqiu; Shen, Mengqin
Highlights: Fatigue mechanism of CFRP reinforced open-hole aluminium plates is experimentally evaluated. Stiffness and crack propagation of interfacial debonding are examined. Fatigue lives are evaluated and suggested for counterpart design based on the BS8118 detail class. Life prediction allowing for effects of carbon fibre and adhesive interface is justified. Abstract: In this paper the characteristics of CFRP reinforcement on the improvement of the fatigue strength of aluminium alloy plates with fastener holes are investigated. The CFRP reinforcement schemes including the number of laminate layers, single-sided and double-sided strengthening are taken into account. Fatigue tests with constant loading amplitude were conducted to compare different failure mechanisms involved with such structural details. The stiffness degradation of test specimen failed by interfacial debonding is shown to be relatively gradual prior to plate rupture while the propagation of the fatigue crack at the transition of the punching surface appears to be retarded to some extent due to the tensile strengthening of the carbon fibre. The contributions of carbon fibre and adhesive interface to the strength improvement are quantified. Discussions are also made for the fatigue life of similar details with some other hole forming methods reported in the literature. Recommendations are given for the assessment of the fatigue life of CFRP reinforced specimens studied herein with appropriate detail classes codified in the BS8118 standard. Finally, a new formula allowing for the contributions of the plate and carbon fibre in tension, the adhesive interface in shear and additional secondary bending effect is proposed in the evaluation of the improvement fatigue endurance. The proposed formula is verified from a good correlation with finite element analytical results and from original test data with a notable reduction of scatters. Its application scope is also discussed.